Potential of B-Cell Epitopes Protein Ag85 Complex Mycobacterium Tuberculosis as Serodiagnostic Antigen of Tuberculosis by in Silico Study - Diana Chusna Mufida; Ayu Munawaroh Aziz; Nurrul Izza Misturiansyah (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: The high case of tuberculosis which isn't followed by good detection becomes an urgency for the diagnostic developments. One of them with immunodiagnostic principle uses B-cell Ag85 complex epitope. The design of the diagnostic epitope was performed by mapping the B cell epitope used in silico studies.Objective: The purpose of this research is to analyze antigenicity, physicochemical which affect immunogenicity, and homology of B-cell Ag85 complex epitope with the strain which circulates in Indonesia. Methods: The samples used were taken from the NCBI protein bank with access numbers P9WQP3 for Ag85A, P9WQP1 for Ag85B, and P9WQN9 for Ag85C. The sequences were analyzed using IEDB (Bepipred) software as the epitope prediction, VaxiJen as antigenicity prediction, ProtParam as physicochemical properties prediction, and BLASTP NCBI as sequence alignment.Results: Twenty seven epitopes were antigenic with 0.4297 to 2.6007 scores and the molecular weight was from 619.59 Da to 3145.36 Da. This research also obtained eleven stable and hydrophilic epitopes. The alignment of 11 candidate epitopes with the strain which circulates in Indonesia, had a similarity percentage of 85.71%-100% and 3 epitopes had a more significant score.Conclusion: Three epitopes of Ag85 complex; Ag85A (212-235), Ag85B (209-237), and Ag85C (283-310), were universal antigens and can be developed into diagnostic antigens in Indonesia.